The Influence of Organizational Career Management, Manager Support and Career Goal commitment on Career Self Management - Ooi , Ing Chyuan (2010)
This study uses cross sectional field data and multiple regression method to investigate the influence of organizational career management, individual\'s career goal commitment and manager\'s support on career self management. The conclusion of this study is that career self management by individual employee can be influenced by organizational career management and individual goal commitment.